Antibacterial Activity and Molecular Docking of Compounds from Avicennia marina Leaves Extracts: Obtained by Natural Deep Eutectic Solvents - Kartikaningsih, Hartati; Djamaludin, Heder; Audina, Nanda; Fauziyah, Jihan Nur (Indonesian Journal of Chemistry, 2024)
This study aims to determine the effect of using natural deep eutectic solvent in extracting compounds from young and old leaves of Avicennia marina on the antibacterial activity through in vitro and in silico. The research method used was experimental with different molar ratios of solvent components: citric acid and glucose (1:1, 2:1, 3:1, 4:1 v/v). In vitro, the paper-disk method was employed to assess percent inhibition, and in silico, peptide deformylase (ID 6JFQ) was the target of the investigation. The best treatment results for testing the antibacterial activity of A. marina leaves extracts that were extracted using natural deep eutectic solvent against S. aureus and E. coli was citric acid and glucose (molar ratio 4:1). The inhibition zone by old leaves extracts was 27.47 and 37.73 mm, and by young leaves extracts were 28.69 and 30.99 mm. Then, phytochemical compound analysis was done using liquid chromatography-mass spectrometry, and six phytochemical compounds were obtained. The docking results showed that the diosmetin 7-O-β-D-glucuronide has the best binding affinity (−9.4 kcal/mol) towards the peptide deformylase. Purification must be done to obtain pure compounds from crude extracts of A. marina leaves.